Symbiotic Bacteria Influence the Odor and Mating Preference of Their Hosts - Richard, Freddie-Jeanne (Frontiers in Ecology and Evolution, 2017)
In many species, chemical communication is a determining factor in mate choice. Some species use the composition of cuticular compounds to discriminate between potential mates. Moreover, the presence of parasites can also influence mate choice and alter the odor of an individual. In the current study, we tested the effect of the endosymbiont Wolbachia, which is naturally present in the terrestrial isopod Armadillidium vulgare and can induce male feminization in the species. We compared male attraction to different types of females (Wolbachia-free, females naturally infected by Wolbachia, Wolbachia-injected females, and females injected with a bacteria-free suspension). Our behavioral assays revealed that males consistently preferred Wolbachia-free females and that this preference correlates to changes in cuticular compounds. Males also preferred naturally infected females over Wolbachia-injected females. The ability of males to discriminate between females could result in Wolbachia impacting its host phenotype, thus affecting the odor of the host. Female odor is the result of an honest signal that makes it possible for males to discriminate between Wolbachia-infected and non-infected females. The male preference for Wolbachia-free females is adaptive, and long-term studies have demonstrated that such choices confer improved fitness.